Pengaruh Slack Resources Dan Gender Dewan Terhadap Kualitas Pengungkapan Tanggung Jawab Sosial Perusahaan - Nadia Dwi Tasya; Charoline Cheisviyanny (Universitas Negeri Padang, 2019)
Tthe objective of this study is to determinethe effect of slack resources and board’s gender on the quality of corporate social responsibility disclosures. The analysis technique uses multiple regression analysis methods. The sample in the study were 28 companies listed on the Indonesia stock exchange and reported sustainability reports for 2015-2017, so that 84 observations were obstained. The results find that slack resources have negative effect on CSR disclosure quality, while the gender on board of directors have positive effect on CSR disclosure quality. There is no relationship between commissioner’s gender and CSR disclosure quality. The control variables used in this study are company size, profitability and leverage, company size and leverage has a influence on CSR disclosure quality while the profitability has no influence on CSR disclosure quality